Effects of Nicotine-Containing E-Cigarette Smoke on Testicular Histopathology in Albino Rats - Nina Amalia; Farodina Azka Zhafira; Maya Nurwartanti Yunita; Shelly Oktania Nurvita Sari; Akbar Dimas Herdiansyah; Selva Pratika; Prasvita Rosa Wardana; Fatimatus Zahro; Aurel Aulia Rahmadani (Universitas Airlangga, 2025)
This study aims to assess the level of damage from histopathology of seminiferous tubules of testicular organs of albino rats affected by exposure to e-cigarette vapor. The 20 albino rats used were divided into 5 groups, which are the control group (C) not given exposure to e-cigarette vapor and the treatment group given exposure to e-cigarette vapor at different doses. Treatment groups T1 (0.3 mg/ml), T2 (3 mg/ml), T3 (12 mg/ml), T4 (36 mg/ml). All treatment groups were given perinhaled and the treatment was carried out for 14 days. At the end of treatment, albino rats were euthanized and then necropsied and testicular organs were preserved to make histopathological preparations using Hematoxilin-Eosin staining. The results of the histopathological picture of the seminiferous tubules of the testes were observed at 400x magnification and the thickness of the epithelium and the diameter of the seminiferous tubules. The results showed a significant change in the thickness of the seminiferous tubule epithelium in each treatment which decreased, but there was no significant change in the diameter of the seminiferous tubules. This study states that exposure to e-cigarette vapor in rats can cause a decrease in spermatogenesis.